The synergistic predictive value of hemoglobin glycation index and SYNTAX score for coronary artery disease complexity and long-term prognosis after percutaneous coronary intervention - Jia, Dongyue; Jiang, Maoling; Feng, Jie; Pan, Junli; Tao, Yuqi; Wang, Sisi; Liu, Si; Liu, Hanxiong; Zhang, Zhen; Xiong, Shiqiang; Cai, Lin (Frontiers in Endocrinology, 2026)
BackgroundThe complexity of coronary artery lesions and glucose metabolic disorders contributes to adverse long-term prognosis following percutaneous coronary intervention (PCI). This study aimed to evaluate the synergistic effect of coronary artery lesions—assessed by the SYNTAX score—and glucose metabolic disorders—quantified by the hemoglobin glycation index (HGI)—on predicting major adverse cardiac and cerebrovascular events (MACCEs) after PCI.MethodsA total of 609 coronary artery disease (CAD) patients undergoing PCI were enrolled in the final analysis. HGI was calculated by subtracting the predicted HbA1c (derived from fasting plasma glucose regression) from the observed HbA1c. Pearson’s coefficients were used for correlation analyses. Kaplan–Meier and Cox regression analyses were used to assess associations with MACCEs. Mediation analysis evaluated whether the SYNTAX score mediated the HGI–MACCEs relationship.ResultsPatients with higher HGI and SYNTAX scores (≥1.16764 and >22, respectively) exhibited a significantly increased mortality risk (p = 0.0052) and more complex coronary lesions. Multivariable analysis confirmed HGI and SYNTAX score as independent predictors of MACCEs. Additionally, the SYNTAX score partially mediated the association between HGI and adverse outcomes, with a mediation proportion of 13.05%.ConclusionThe HGI and SYNTAX score exert a synergistic effect in predicting the severity of CAD and the risk of adverse prognosis after PCI. It highlights the necessity of integrating both metabolic and anatomical assessment indices for comprehensive risk stratification of CAD patients undergoing PCI.